How spatial constraints afford successful and unsuccessful penetrative passes in elite association football - Travassos, Bruno (2022)
Background: The aim of the present study was to examine the spatial relations between teams (macro- level) and groups of players (meso-level) that afford successful penetrative passes (off-ball advantage) in elite football. Methods: Three balanced home matches from a Premier League team with 91 ball possessions in which a pass was performed into the opposition defensive area and overpassed the first defensive line, promoting a perturbation of the defensive team equilibrium, were selected for analysis. The spatial relations between teams were measured through spatial variables that captured the areas occupied by the teams, while the spatial relations between players were measured through variables that captured the distances and angles between attacking and defending players near the ball. Results: Results revealed, at the macro-level, higher values of width ratio between teams and the width of the attacking team for unsuccessful penetrative passes (UPP), when compared to successful pene- trative passes (SPP). At the meso-level, a general decrease in distances and an increase in angles between attacking and defending players were observed between successful to unsuccessful penetrative passes. Conclusions: These findings highlight the importance of using positional data analysis to identify teams’ tactical profiles and to potentiate coaches’ interventions.